Liquid-metal-electrode-assisted electrolysis for the production of sodium and magnesium - Lei Guo; Huayi Yin; Wenmiao Li; Shiyu Wang; Kaifa Du; Hao Shi; Xu Wang; Dihua Wang (Journal of Magnesium and Alloys)
Sodium (Na) and magnesium (Mg) are becoming important for making energy-storage batteries and structural materials. Herein, we develop a liquid-metal-electrode-assisted electrolysis route to producing Na and Mg with low-carbon emissions and no chlorine gas evolution. The clean production stems from the choice of a molten NaCl-Na2CO3 electrolyte to prevent chlorine gas evolution, an inert nickel-based anode to produce oxygen, and a liquid metal cathode to make the cathodic product sit at the bottom of the electrolytic cell. We achieve a current efficiency of >90% for the electrolytic production of liquid Na-Sn alloy. Later, Mg-Sn alloy is prepared using the obtained Na-Sn alloy to displace Mg from molten NaCl-MgCl2 with a displacement efficiency of >96%. Further, Na and Mg are separated from the electrolytic Na-Sn and displaced Mg-Sn alloys by vacuum distillation with a recovery rate of >92% and Sn can be reused. Using this electrolysis-displacement-distillation (EDD) approach, we prepare Mg from seawater. The CO2 emission of the EDD approach is ∼20.6 kg CO2 per kg Mg, which is less than that of the Australian Magnesium (AM) electrolysis process (∼25.0 kg CO2 per kg Mg) and less than half that of the Pidgeon process (∼45.2 kg CO2 per kg Mg).